A Rare Coexistence of Bilateral Congenital Wilms Tumor with Ductal Plate Malformation at Autopsy. (3rd May 2016) - Mitra, Suvradeep; Chatterjee, Debajyoti; Gowda, Kiran; Das, Ashim
ABSTRACT: Congenital Wilms tumor is a tumor of childhood. Here we present an unusual case of bilateral congenital Wilms tumor with associated ductal plate malformation. In addition, there was also associated oligohydramnios, pulmonary hypoplasia, and multiple skeletal anomalies in this index case. Although various syndromic associations of Wilms tumor are well described in the literature, an association of congenital Wilms tumor with ductal plate malformation, polysplenia, and skeletal malformations is not reported. We believe that this is the first reported case of such an association.